Comparative Analysis of Human and Porcupine (Hystrix Cristata L., 1758) Haemoglobins - Cigremis, Yilmaz; Atalar, Omer; Erdogan, Kenan; Gaffaroglu, Muhammet; Turkoz, Yusuf; Yilmaz, Sadik (Gazi Univ, 2008)
Agarose gel electrophoresis was used to determine the electrophoretic pattern of the haemoglobin of Hystrix cristata (H. cristata), and that of a healthy human. Alkaline agarose gel electrophoresis of the haemoglobin of H. cristata revealed that the mobility of the H. cristata haemoglobin was considerably faster than that of human haemoglobin. These comparisons showed obvious differences between the haemoglobin of the two species.
Keywords: Hystrix cristata; Haemoglobin; Electrophoresis